Spinal cord morphology and PKD2L1+ cells distribution: effects of age, sex, and spinal segment in mice - Leblond, Lugdivine; Ramirez-Franco, Jorge; Michelle, Caroline; Wanaverbecq, Nicolas; Evin, Morgane (Frontiers in Neuroanatomy, 2025)
IntroductionMorphometrical studies of the mouse spinal cord are often limited to one age or sex, restricting our understanding of anatomical variability. This study provides a detailed analysis of the spinal cord in mice, examining the effects of age, sex, and spinal region, along with the distribution of PKD2L1-positive (PKD2L1+) cells along the rostro-caudal axis.MethodsUsing 811 transverse sections from a total of 18 3- and 8-week-old mice, DAPI immunofluorescence and confocal imaging, 14 dimensions of gray matter (GM), white matter (WM), and the central canal (CC) were assessed using landmarks positioning and segmentation methods.ResultsAge was the most influential factor: between 3- and 8- weeks-old, the spinal cord showed reduced rostro-caudal length (p = 2.49e-04), smaller ventral GM horns (p < 0.005), deeper ventral commissures (p = 5.58e-13), and an increase in CC area (from 1925.58 ± 630.16 μm2 to 2199.50 ± 569.44 μm2). Looking at sex-related differences, females showed higher variability across several parameters, with subtle differences in GM organization (p < 0.05) and CC morphology (mean area = 2146.39 ± 632.91 μm2 in females vs. 1998.36 ± 589.85 μm2 in males). Along the rostro-caudal axis, WM size, as well as GM dorsal and ventral horn dimensions, differed significantly across spinal segments (p < 0.005). CC position also shifted dorsally in cervical and lumbar regions depending on age and sex (p < 0.005). PKD2L1+ cells were mainly clustered near the CC, with over 46% located proximally. The highest densities (>300 cells/segment) were found in lumbar and lower thoracic regions.DiscussionThese results indicate progressive structural changes during development, including reorganization of cells and CC architecture stabilization. The distribution of PKD2L1+ cells is consistent with their proposed role as cerebrospinal fluid-contacting neurons potentially involved in sensing fluid composition and modulating locomotor control. Their increased presence in caudal segments suggests functional specialization in different spinal regions.ConclusionThis work provides detailed, segment-specific anatomical data crucial for developing accurate and physiological numerical models. Adding age and sex differences emphasizes the need to reflect biological variability in simulations. Additionally, the mapping of PKD2L1+ neurons offers valuable insight into their spatial organization and potential involvement in sensory processing, locomotor function, and neurological or developmental disorders.